Portrait of Portugal’s Nut Iii Regions in Productive Location Clusters - Diniz, Francisco José Lopes de souse; Sequeira, Maria Teresa Couceiro da Costa Sequeira e Sousa (Economy of Regions, 2015)
The purpose of this article is to piece together a picture of Portuguese regions at the end of the first decade of the twenty-first century. In particular, the authors tried to group NUT III regions according to the location of productive activities bearing in mind employment and other economic and social indicators, namely productivity and purchasing power, as well as competitiveness and environmental quality indicators. Using clusters, it was possible to obtain a map of Portugal containing 6 cluster typologies. Clearly, at one end of these typologies are the regions where tertiary activities are predominant and where there is more purchasing power, productivity and competitiveness, causing, however, more damages to the environment, whereas at the other end are the rural less competitive regions with a lower purchasing power but environmentally more attractive. In between, there are other situations which are also looked into.